2016
DOI: 10.1016/j.jmbbm.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multi-scale mineralized collagen–polycaprolactone composites for bone tissue engineering

Abstract: A particular challenge in biomaterial development for treating orthopedic injuries stems from the need to balance bioactive design criteria with the mechanical and geometric constraints governed by the physiological wound environment. Such trade-offs are of particular importance in large craniofacial bone defects which arise from both acute trauma and chronic conditions. Ongoing efforts in our laboratory have demonstrated a mineralized collagen biomaterial that can promote human mesenchymal stem cell osteogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 60 publications
2
65
0
1
Order By: Relevance
“…We have previously shown that while hydrated CG scaffolds show reduced elastic moduli than non-hydrated scaffolds, the hydrated and dry scaffolds all show characteristic stress-strain behavior characteristic of low-density, open-cell foams (Caliari et al, 2015b; Caliari et al, 2014; Harley et al, 2007; Weisgerber et al, 2013a). Further, we have shown that composites formed from collagen scaffolds and polycaprolactone (PCL) support frame show identical mechanical performance in the dry and hydrated state due to the presence of the PCL phase (Weisgerber et al, 2016). While we do not expect significant short-term changes in the mechanical performance of the PLA-collagen composite due to the slow hydrolytic degradation of PLA, the ability to separately tailor the degradation characteristics of the CG scaffold via chemical crosslinking across a wide range (<2wks to >2 years) of half-lives (Harley et al, 2004) suggests future efforts to match PLA and collagen degradation rates with new tissue formation.…”
Section: : Discussionmentioning
confidence: 99%
“…We have previously shown that while hydrated CG scaffolds show reduced elastic moduli than non-hydrated scaffolds, the hydrated and dry scaffolds all show characteristic stress-strain behavior characteristic of low-density, open-cell foams (Caliari et al, 2015b; Caliari et al, 2014; Harley et al, 2007; Weisgerber et al, 2013a). Further, we have shown that composites formed from collagen scaffolds and polycaprolactone (PCL) support frame show identical mechanical performance in the dry and hydrated state due to the presence of the PCL phase (Weisgerber et al, 2016). While we do not expect significant short-term changes in the mechanical performance of the PLA-collagen composite due to the slow hydrolytic degradation of PLA, the ability to separately tailor the degradation characteristics of the CG scaffold via chemical crosslinking across a wide range (<2wks to >2 years) of half-lives (Harley et al, 2004) suggests future efforts to match PLA and collagen degradation rates with new tissue formation.…”
Section: : Discussionmentioning
confidence: 99%
“…With special attention to risk factors and their connection to the principles of prevention and treatment, surgeons care more and more about the major long-term complications, reliable and safe implant, rhythm of resorbability and measures implemented in practice to minimize the sequelae [8, 9]. As a result of these concerns, biomaterials of choice entail attributes of excellent osteoconductivity, biocompatibility and additional properties like radiolucency, antibiosis, free of immunologic rejection, poor thermal conductivity and ability to induce osteanagenesis [10]. Fracture, non-union, collapse, subluxation and any other joint injury requiring reparative regeneration of osseous tissues indicate application of mineralized collagen artificial bone repair material products that are endued with all the merit of an ideal biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…With crystallized hydroxyapatite arrayed along fibrils of type I collagen, mineralized collagen fabricates the understructure of the hardest human connective tissues such as bone and dentin [10, 11]. Within the mineralized collagen, hydroxyapatite crystals with size on nanometer scale orderly juxtapose along fibrils fabricated from type I collagen in a specific hierarchically staggered nanostructure.…”
Section: Discussionmentioning
confidence: 99%
“…Mineralized collagen scaffolds were fabricated using previously described procedures 10,11,21,27,[40][41][42][43][44][45] . In a cooled, jacketed vessel, 1.9 w/v% type I bovine collagen (Sigma-Aldrich, Missouri, USA), 0.84 w/v% chondroitin-6-sulfate (Sigma-Aldrich), and Ca(OH)2, H3PO4, and Ca(NO3)2·4H2O were thoroughly homogenized, making sure to prevent collagen clumping.…”
Section: Fabrication Of Isotropic and Anisotropic Mineralized Collagementioning
confidence: 99%
“…Sectioned scaffolds were placed onto glass slides and stained with an aniline blue solution (Thermo Fisher Scientific, Massachusetts, USA) to stain collagen fibers. Slides were then imaged with a NanoZoomer Digital Pathology System (Hamamatsu, Japan) and pore structure was analyzed with a custom Matlab pore size code to acquire an average pore size and pore aspect ratio for each scaffold 30,41 .…”
Section: Sem Imaging and Pore Size Analysis Of Mineralized Collagen Smentioning
confidence: 99%